2005
DOI: 10.1172/jci26845
|View full text |Cite
|
Sign up to set email alerts
|

B cells: no longer bystanders in liver fibrosis

Abstract: Cytokines secreted by cells that mediate the innate and adaptive immune responses play a critical role in regulating the synthesis of ECM components by fibroblasts. Overexpression and deposition of ECM components are dominant features of fibrotic diseases, including hepatic fibrosis. The contribution of CD4 + Th2 cells to hepatic fibrosis has been well described. Now, in this issue of the JCI, Novobrantseva et al. provide data to suggest that hepatic B cells also play a role in liver injury (see the related ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
(34 reference statements)
0
38
1
Order By: Relevance
“…10 Our results found the association between SMA seropositivity and advanced fibrosis (F3-F4) that may be an additional evidence of the involvement of the Th2 immune response in the active fibrogenesis as previously revised. 11 The association between SMA and advanced fibrosis was also reported in a recent study performed with French HCV carriers, which also demonstrated an association between the presence of SMA and hepatocellular necrosis and inflammation, 12 a finding that was not verified in our work. Such a divergence related to hepatic necroinflammation may be caused by ethnic difference in the populations studied or by difference in the genetic background of the HCV carriers investigated.…”
Section: Discussioncontrasting
confidence: 44%
“…10 Our results found the association between SMA seropositivity and advanced fibrosis (F3-F4) that may be an additional evidence of the involvement of the Th2 immune response in the active fibrogenesis as previously revised. 11 The association between SMA and advanced fibrosis was also reported in a recent study performed with French HCV carriers, which also demonstrated an association between the presence of SMA and hepatocellular necrosis and inflammation, 12 a finding that was not verified in our work. Such a divergence related to hepatic necroinflammation may be caused by ethnic difference in the populations studied or by difference in the genetic background of the HCV carriers investigated.…”
Section: Discussioncontrasting
confidence: 44%
“…Both protocol and indication biopsies beyond 6 months posttransplant often manifest an increase in B-cell nodules as well as scarring (15,22,26,28 g. IL4, IL6, IL13), potentially through collagen production and fibroblast proliferation (10,33,34 …”
Section: Infiltrates and Scarringmentioning
confidence: 99%
“…Different liver cell populations and molecular mechanisms are activated depending upon the extent and nature of the damage to the liver (mild or severe), the underlying liver disease (acute or chronic), and the type of damage (with or without necrosis, inflammation; Bhogal and Bona 2005). Recent studies indicate that the expression of the cell surface protein, Thy-1 (CD 90), is induced in fibroblast populations associated with wound healing and fibrosis in several tissues, e.g., during the transformation of keratocytes to corneal fibroblasts and myofibroblasts (MFs; Saalbach et al 1999;Pei et al 2004).…”
Section: Introductionmentioning
confidence: 99%